Assessment of functional capacity and sleep quality of patients with chronic heart failure - Taofeek O. Awotidebe, PhD, PT; Victor O. Adeyeye, MBChB, FWACP; Rufus A. Adedoyin, PhD, PT; Suraj A. Ogunyemi, MBChB, FWACP; Kayode I. Oke, PhD, PT; Rita N. Ativie, MSc, PT; Goodness B. Adeola, BMR, PT; Mukadas O. Akindele, PhD, PT; Michael O. Balogun, MBChB, FWACP (World Scientific Publishing, 2017)
Background: Adequate sleep improves physical and mental alertness. However, there is a dearth of empirical data on functional capacity (FC) and sleep quality (SpQ) in patients with chronic heart failure (CHF). Objective: This study investigated the relationship between FC and SpQ of patients with CHF and apparently healthy controls (HCs). Methods: This case-control study recruited 50 patients with CHF whose left ventricular ejection fraction (LVEF) was <40%, attending cardiac clinics of selected government hospitals in Osun State. Furthermore, 50 age- and sex-matched healthy individuals were recruited as controls. Socio-demographic characteristics and cardiovascular parameters were assessed. The FC (VO2 max) and SpQ were assessed using the 6-minute walk test (6-MWT) and Pittsburgh Sleep Quality Index (PSQI), respectively. Data were analysed using descriptive and inferential statistics. Alpha level was set at p < 0.05. Results: Patients had a significantly lower FC and poorer SpQ than HCs, 4.6 ± 0.5 versus 11.3 ± 1.6 mL/kg/min (t = −3.452; p = 0.001) and 8.74 ± 1.6 versus 3.8 ± 1.3 (t = −5.371; p = 0.001), respectively. HCs were about five times more likely to walk longer distance [odds ratio (OR), 4.8; confidence interval (CI), 2.0-11.1] and had a better heart rate (OR, 2.8; CI, 1.4-5.3) than patients. SpQ had a significant negative correlation with FC of patients (r = −0.362; p = 0.001) but a significant positive correlation with HCs (r = 0.481; p = 0.041). Furthermore, there were significant correlations between FC and body mass index in both groups (CHF: r = 0.247, p = 0.022; HCs: r = 0.321, p = 0.040). Conclusion: Patients with heart failure demonstrated lower functional capacity and poorer sleep quality.